2007
DOI: 10.1111/j.1360-0443.2006.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Methadone maintenance treatment: the balance between life‐saving treatment and fatal poisonings

Abstract: The 'high threshold programme' is safe as long as the patients remain in treatment and there are very few deaths due to leakage from the programme. However, there is a high mortality among those discharged from the programme and only a minority of the heroin users in Stockholm had applied for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 19 publications
4
74
0
3
Order By: Relevance
“…We observed an increase in the number of methadone-related deaths in recent years which is consitent with the findings of many other investigators [6,9,17,18,22]. One author however found a decrease [16] -but this finding may result from only a small collective.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We observed an increase in the number of methadone-related deaths in recent years which is consitent with the findings of many other investigators [6,9,17,18,22]. One author however found a decrease [16] -but this finding may result from only a small collective.…”
Section: Discussionsupporting
confidence: 62%
“…Among the long-term studies [6,7,8,10] with an observation period of 10 years or more with 146 deceased we investigated a relatively large number of cases. However, some shorter studies of five years in length or less presented data with an even larger number of victims [5,18].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of drug‐related deaths are among individuals not in treatment 22, 56. Restricting access to OST is associated with high rates of mortality among opioid‐dependent people who have been discharged or denied treatment 57. Open access to OST is a feature of the ‘British System’ of drug treatment and a response to HIV/AIDS epidemic in the early 1990s 58.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients who leave methadone programmes have increased mortality risks relative to those remaining in treatment. ( Caplehorn, Dalton, Haldar, Petrenas, & et al, 1996;Clausen, Anchersen, & Waal, 2008;Davoli, et al, 2007;Fugelstad, Stenbacka, Leifman, Nylander, & Thiblin, 2007;Langendam, van Brussel, Coutinho, & van Ameijden, 2001;Zanis & Woody, 1998) A recent prospective cohort study of Italian opiate users found that the risk of overdose following treatment cessation was more than three times higher in the first 30 days after treatment drop-out or discharge compared to the subsequent 31 days or more after treatment. (Davoli, et al, 2007) However, these effects are not specific to MMT but rather a range of treatments for heroin dependence, including MMT, methadone detoxification, other pharmacological detoxification and psychological interventions.…”
Section: Introductionmentioning
confidence: 99%